A novel concept of two-component dielectric function for gold nanostars: theoretical modelling and experimental verification. Issue 38 (30th September 2020) - Khlebtsov, Nikolai G.; Zarkov, Sergey V.; Khanadeev, Vitaly A.; Avetisyan, Yuri A.
Abstract : We have introduced a new two-component dielectric function for modelling of gold nanostars. Abstract : Rational design of AuNST morphology requires adequate computational models. The bulk dielectric function is not applicable to sharp nanostar spikes. We suggest a two-component dielectric function in which the nanostar core is treated as a bulk material, whereas the size-corrected dielectric function of the spikes is treated by a modified Coronado–Schatz model. In addition to the strong broadening of plasmonic peaks, the simulated absorption and scattering spectra show unusual properties, which are not observed with bulk dielectric functions. The effect of NIR water absorption on nanostar spectra is small, and the absorption peak demonstrates the expected small decrease in the absorbing media. Surprisingly, however, water absorption increases the scattering peak by 30%. For the common surfactant-free Vo-Dinh AuNSTs, we report, for the first time, very intense SWIR plasmonic peaks around 1900 nm, in addition to the common strong peak in the UV–vis–NIR band (here, at 1100 nm). For bilayers of AuNSTs in air, we recorded two similarly intense peaks near 800 and 1500 nm. To simulate the experimental extinction spectra of colloids and bilayers on glass in air, we develop a statistical model that includes the major fraction of typical Vo-Dinh AuNSTs and two minor fractions of sea urchins and particles with protrusions. In contrast to the general belief, we show that the common UV–vis–NIR plasmonic peak of surfactant-free AuNSTs is related to short spikes on a spherical core, whereas long spikes produce an intense SWIR plasmonic mode. Such a structural assignment of vis–NIR and SWIR peaks does not seem to have been reported previously for surfactant-free nanostars. With our model, we demonstrate good agreement between simulated and measured spectra of colloids and bilayers on glass in air.